Recent Developments in Fish Processing and Preservation - PILLAI, V. K. (Fishery Technology, 1966)
The paper outlines the major developments that have taken place in the fish preservation and processing fields. Many of these can profitably be applied to the prawn processing industry. Competition in the world market for the conventional types of frozen and canned products is on the increase and only top quality at lesser price will be able to sustain the industry. Consumer type packs of individually frozen prawn in aluminum lined polythene bags, boilable plastic bags, breaded prawn products etc. are becoming increasingly popular in the Western countries. Considering the potentialities of our prawn processing industry it is only justifiable that we start work on these lines without delay.